Parallel execution of a parameter sweep for molecular dynamics simulations in a hybrid GPU/CPU environment - García Garino, Carlos (2012)
Molecular Dynamics (MD) simulations can help to utimingnderstand an immense number of phenomena at the nano and microscale. They often require the exploration of large parameter space, and a possible parallelization strategy consists of sending different parameter sets to different processors. Here we present such approach using a hybrid environment of Graphic Processing Units (GPUs) and CPU cores. We take advantage of the software LAMMPS (lammps.sandia.gov), which is already prepared to run in a hybrid environment, in order to do an efficient parameter sweep. One example is presented in this work: the collision of two clusters is sampled over a multivariate space to obtain information on the resulting structural properties.